Abnormalities of cerebral perfusion in multiple sclerosis. Issue 9 (16th August 2004) - Rashid, W; Parkes, L M; Ingle, G T; Chard, D T; Toosy, A T; Altmann, D R; Symms, M R; Tofts, P S; Thompson, A J; Miller, D H
Abstract : Background: Measuring perfusion provides a potential indication of metabolic activity in brain tissue. Studies in multiple sclerosis (MS) have identified areas of decreased perfusion in grey matter (GM) and white matter (WM), but the pattern in clinical subgroups is unclear. Objectives: This study investigated perfusion changes in differing MS clinical subgroups on or off β-interferon therapy using a non-invasive MRI technique (continuous arterial spin labelling) to investigate whether different clinical MS subtypes displayed perfusion changes and whether this could give a further insight into the pathological mechanisms involved. Methods: Sixty patients (21 relapsing remitting, 14 secondary progressive, 12 primary progressive, 13 benign) and 34 healthy controls were compared. Statistical parametric mapping (SPM '99) was used to investigate regional variations in perfusion in both GM and WM. Global WM perfusion was derived by segmenting WM from images using T1 relaxation times. Results: Regions of lower perfusion in predominantly GM were observed in the primary and secondary progressive cohorts, particularly in the thalamus. Increased WM perfusion was seen in relapsing remitting and secondary progressive cohorts. Conclusions: Low GM perfusion could reflect decreased metabolism secondary to neuronal and axonal loss or dysfunction with a predilection for progressive forms of MS. Increased WM perfusion may indicate increased metabolic activity possibly due to increased cellularity and inflammation. Improved methodology and longitudinal studies may enable further investigation of regional and temporal changes, and their relationship with physical and cognitive impairment.